Comparative Study of the Mining Tax Regime for Mineral Exploitation in Kazakhstan - Ostensson, Olle; Parsons, Bob; Dodd, Samantha (World Bank, Washington, DC, 2015)
Kazakhstan is rich in both minerals and hydrocarbons. While the hydrocarbons sector is relatively successful, the minerals sector has failed to achieve its potential. Despite large mineral reserves, very little investment has gone into the development of new mining projects and few foreign investors have been willing to invest in the sector. Almost all mines currently operating in Kazakhstan were already in operation in the 1990s, leaving a two decade gap in new mine development. Mining policy in Kazakhstan does not prioritize only revenue generation but aims at promoting employment, skills development and economic diversification. In order to achieve these goals Kazakhstan will have to attract foreign investment into the sector. There are several elements to the current mineral legislation and fiscal regime that are unusual in an international context and act as a deterrent to foreign investment. This report carries out a comparative analysis of Kazakhstan's mineral regime and makes recommendations on changes that could be made to the existing regime to bring it in line with international good practice. Kazakhstan's fiscal regime is compared to twelve other countries and to global trends in mineral regimes.